Blood transfusion. (April 2017) - Booth, Catherine; Allard, Shubha
Abstract: The term 'blood transfusion' generally refers to therapeutic use of whole blood or its components (red cells, platelets, fresh frozen plasma, cryoprecipitate). Careful donor selection and stringent testing by the blood service is required to ensure a safe blood supply. Blood transfusion can be life-saving in many clinical treatments. However, donated blood is a limited resource, and hospital blood transfusion practice must focus on ensuring safe and appropriate use. Patient Blood Management is an evidence-based multidisciplinary approach aimed at optimizing care of patients who might need transfusion to reduce avoidable use of blood components. Clinical guidelines are essential in all specialties using blood and components, supported by education and training with regular practice audits. To minimize errors, particular emphasis must be placed on accurate patient identification throughout, from the initial blood sample, through laboratory testing and transfer of blood to clinical areas, to the final bedside check before transfusion. The reporting and monitoring of all blood transfusion adverse events via national haemovigilance schemes has highlighted key areas for action and improved transfusion safety. Transfusion medicine must be practised within a strict regulatory framework; the Blood Safety and Quality Regulation 2005 based on European Union blood directives has had particularly far-reaching implications for UK blood services and hospital transfusion laboratories.